Frontiers of Sodium MRI Revisited: From Cartilage to Brain Imaging. Issue 1 (26th August 2020) - Zaric, Olgica; Juras, Vladimir; Szomolanyi, Pavol; Schreiner, Markus; Raudner, Marcus; Giraudo, Chiara; Trattnig, Siegfried
Abstract : Sodium magnetic resonance imaging ( 23 Na‐MRI) is a highly promising imaging modality that offers the possibility to noninvasively quantify sodium content in the tissue, one of the most relevant parameters for biochemical investigations. Despite its great potential, due to the intrinsically low signal‐to‐noise ratio (SNR) of sodium imaging generated by low in vivo sodium concentrations, low gyromagnetic ratio, and substantially shorter relaxation times than for proton ( 1 H) imaging, 23 Na‐MRI is extremely challenging. In this article, we aim to provide a comprehensive overview of the literature that has been published in the last 10–15 years and which has demonstrated different technical designs for a range of 23 Na‐MRI methods applicable for disease diagnoses and treatment efficacy evaluations. Currently, a wider use of 3.0T and 7.0T systems provide imaging with the expected increase in SNR and, consequently, an increased image resolution and a reduced scanning time. A great interest in translational research has enlarged the field of sodium MRI applications to almost all parts of the body: articular cartilage tendons, spine, heart, breast, muscle, kidney, and brain, etc., and several pathological conditions, such as tumors, neurological and degenerative diseases, and others. The quantitative parameter, tissue sodium concentration, which reflects changes in intracellular sodium concentration, extracellular sodium concentration, and intra–/extracellular volume fractions is becoming acknowledged as a reliable biomarker. Although the great potential of this technique is evident, there must be steady technical development for 23 Na‐MRI to become a standard imaging tool. The future role of sodium imaging is not to be considered as an alternative to 1 H MRI, but to provide early, diagnostically valuable information about altered metabolism or tissue function associated with disease genesis and progression. Level of Evidence: 1 Technical Efficacy Stage: 1